Discovery of novel quinoline sulphonamide derivatives as potent, selective and orally active RORγ inverse agonists. Issue 14 (15th July 2019) - Amaudrut, Jérôme; Argiriadi, Maria A.; Barth, Martine; Breinlinger, Eric C.; Bressac, Didier; Broqua, Pierre; Calderwood, David J.; Chatar, Mohamed; Cusack, Kevin P.; Gauld, Stephen B.; Jacquet, Sébastien; Kamath, Rajesh V.; et al.
Graphical abstract: Abstract: A high-throughput screen against Inventiva's compound library using a Gal4/RORγ-LBD luciferase reporter gene assay led to the discovery of a new series of quinoline sulphonamides as RORγ inhibitors, eventually giving rise to a lead compound having an interesting in vivo profile after oral administration. This lead was evaluated in a target engagement model in mouse, where it reduced IL-17 cytokine production after immune challenge. It also proved to be active in a multiple sclerosis model (EAE) where it reduced the disease score. The synthesis, structure activity relationship (SAR) and biological activity of these derivatives is described herein.